Performance Evaluation of Distributed Extended KDamper Devices for Seismic Protection of Mid-Rise Building Structures - Kapasakalis, K.; Mantakas, A.; Kalderon, M.; Antoniou, M.; Sapountzakis, E. J. (Journal of earthquake engineering : JEE, 2024)
This study proposes a novel seismic protection strategy that applies and distributes extended KDamper devices (d-EKD) along the height of an existing mid-rise building structure. The performance of the d-EKD is assessed on a set of real earthquake records and is compared to a system with optimally distributed Tuned Mass Dampers (d-TMD). The proposed framework with the d-EKDs manages to outperform the d-TMDs, regardless the number of installed devices, further reducing the structure's dynamic responses by more than5%, using0 times lower total additional masses, rendering it a realistic and compelling alternative for passive seismic protection.